Neonatal hypoglycemia and the CPT1A P479L variant in term newborns: A retrospective cohort study of Inuit newborns from Kivalliq Nunavut. Issue 4 (3rd April 2020) - Collins, Sorcha A; Hildes-Ripstein, Gertrude Elizabeth; Thompson, James Robert; Edmunds, Sharon; Miners, Amber; Rockman-Greenberg, Cheryl; Arbour, Laura
Abstract: Introduction: Neonatal hypoglycemia (NH) in the first days of life can largely be prevented by recognizing those at risk and managing accordingly. The CPT1A P479L variant is prevalent in northern Indigenous populations and is a possible risk factor for hypoglycemia. We report on NH incidence in the Kivalliq region of Nunavut, where all Inuit newborns are screened for NH. Methods: We reviewed clinical charts of 728 Inuit newborns from Kivalliq (January 1, 2010 to December 31, 2013) for blood glucose (BG) levels and infant/maternal characteristics, linking to CPT1A genotype; 616 newborns had BG data from 2 to 48 hours of life. NH was defined using Canadian Paediatric Society guidelines (≤2.0 mmol/L at 2 hours, <2.6 mmol/L at 2 to 48 hours). Results: NH was documented in 21.4% overall, 24.4% of at-risk newborns and 19.5% of term newborns with no risk factors (≥37 weeks gestation, term-NRF). NH was documented in 22.0% of CPT1A P479L homozygous, 19.8% of P479L heterozygous and 4.8% of noncarrier term-NRF newborns. With multivariable logistic regression, the adjusted ORs for developing NH in term-NRF newborns was 4.97 for CPT1A P479L homozygotes (95% confidence interval [CI]:0.65–38.35, P=0.19) and 4.71 for P479L heterozygotes (95% CI:0.57–37.89, P=0.15). Conclusion: Term-NRF newborns had a higher NH incidence than previously reported, similar to that for at-risk newborns, possibly due to the CPT1A P479L variant. Since only Inuit newborns from Kivalliq are screened for NH, further study of long-term outcomes of NH in this population and the role of the P479L variant are warranted to determine if neonatal BG screening is indicated in all Inuit newborns.